2023
DOI: 10.1039/d2sc05960f
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free synthesis of diverse fluorescent polyoxadiazoles for the facile formation and morphology visualization of microporous films and cell imaging

Abstract: The development of facile polymerizations toward functional heterocyclic polymers is of great significance for chemistry and materials science. As an important branch of heterocyclic polymers, polyoxadiazoles (PODs) have found applications...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Although several green/sustainable catalysts have been invented for multicomponent reactions, 1 c ,25 the development of new multicomponent protocols under catalyst-free, energy-efficient conditions is a highly anticipated task for the construction of a variety of organic compounds. 42…”
Section: Multicomponent Reactionsmentioning
confidence: 99%
“…Although several green/sustainable catalysts have been invented for multicomponent reactions, 1 c ,25 the development of new multicomponent protocols under catalyst-free, energy-efficient conditions is a highly anticipated task for the construction of a variety of organic compounds. 42…”
Section: Multicomponent Reactionsmentioning
confidence: 99%
“…One of the aggregation-induced emission (AIE) materials have always been a hot topic in optical material research. With the increasing maturity of AIE effect research, a large number of AIE effect molecular structures have been reported. At the same time, the application of the AIE effect is constantly being updated. For example, Han et al used simple organic compounds to form supramolecular self-assembled hydrogels with AIE characteristics through intermolecular forces and showed reversible sol–gel transition under temperature or pH induction. By mixing with the fluorescent dye RhB, a light trapping gel system with high FRET (fluorescence resonance energy transfer) efficiency and fluorescence quantum yield was produced .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many MCRs have been widely used in the development of new functional polymers. These MCRs include the Passerini [1,2], Ugi [3,4], Biginelli [5][6][7], Kabachnik-Fields [8,9], Hantzsch [10,11], and Mannich reactions [12,13] as well as thiolactone-based [14] and metal-catalyzed multicomponent reactions [15]. The functional polymers prepared by means of these MCRs have been further applied in the fields of environmental science [16,17], material science [18,19], and biomedicine [20].…”
Section: Introductionmentioning
confidence: 99%